1990
DOI: 10.1007/bf00973755
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord ischemia-induced elevation of amino acids: Extracellular measurement with microdialysis

Abstract: Excitatory amino acids have been implicated in the production of calcium mediated neuronal death following central nervous system ischemia. We have used microdialysis to investigate changes in the extracellular concentrations of amino acids in the spinal cord after aortic occlusion in the rabbit. Glutamate, aspartate, glutamine, asparagine, glycine, taurine, valine, and leucine were measured in the microdialysis perfusate by high pressure liquid chromatography. The concentrations of glutamate, glycine, and tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Several studies have shown a rapid elevation of the extracellular concentration of glutamate and aspartate in traumatic 38,39 and ischemic 40 spinal cord lesions consistent with the hypothesis that these lesions are associated with a release of these excitatory amino acids at the lesion site. In the weight-drop model, Demediuk et al (1989) observed increased extracellular glutamate and aspartate as early as 5 min after SCI and found that the release of these amino acids was delayed, time-dependent and related to the severity of injury.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have shown a rapid elevation of the extracellular concentration of glutamate and aspartate in traumatic 38,39 and ischemic 40 spinal cord lesions consistent with the hypothesis that these lesions are associated with a release of these excitatory amino acids at the lesion site. In the weight-drop model, Demediuk et al (1989) observed increased extracellular glutamate and aspartate as early as 5 min after SCI and found that the release of these amino acids was delayed, time-dependent and related to the severity of injury.…”
Section: Discussionsupporting
confidence: 58%
“…This evidence includes: 1. The significant increase in EAA levels during the first ten minutes after ischaemia [93,94]; 2. The distribution of ischaemic damage coincides with the distribution of EAA receptors in several brain areas [95]; 3.…”
Section: Glutamate Neurotoxicitymentioning
confidence: 99%
“…GSH was measured by the method of Tietze (30) by using a COBAS-BIO centrifugal analyzer (Roche Diagnostics). Plasma amino acid levels were measured as previously described (31 coat color. These chimeras were mated, and genotype analysis of agouti offspring with the 3' DNA probe revealed the presence of the 6.5-kb band diagnostic of the mutant allele.…”
mentioning
confidence: 99%